2010
DOI: 10.14219/jada.archive.2010.0258
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners' Use of Caries-Preventive Agents in Adult Patients Versus Pediatric Patients

Abstract: Background Evidence suggests that caries prevention reduces caries in adults. This study tested the frequency of recommended caries prevention agents for children compared to adult patients. Methods This study surveyed 467 Dental Practice-Based Research Network general dentists who practice within the United States and treat both pediatric and adult patients. Dentists were asked the percentage of their patients who are administered or recommended dental sealants, in-office and at-home fluoride, chlorhexidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Other commonly used preventive agents include topical fluorides, which could also be used in adults at home, in medical or dental settings. A national dental practice‐based research network recently demonstrated that most general practitioners do not offer topical fluorides to patients in their offices but promote their use at home 41 . In addition to topical applications, water fluoridation can also play a role in edentulism prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other commonly used preventive agents include topical fluorides, which could also be used in adults at home, in medical or dental settings. A national dental practice‐based research network recently demonstrated that most general practitioners do not offer topical fluorides to patients in their offices but promote their use at home 41 . In addition to topical applications, water fluoridation can also play a role in edentulism prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A national dental practice-based research network recently demonstrated that most general practitioners do not offer topical fluorides to patients in their offices but promote their use at home. 41 In addition to topical applications, water fluoridation can also play a role in edentulism prevention. An English study found that water fluoridation reduces tooth decay in adolescents and reduces the dental health disparities between socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite established efficacy, professionally applied fluoride varnish has not had widespread practice . In countries with community water fluoridation such as Australia, the Republic of Ireland and the US, fluoride varnish is recommended for elevated caries risk, whereas in countries with limited or no water fluoridation such as England and Scotland, fluoride varnish is recommended for all children and young adults .…”
Section: Introductionmentioning
confidence: 99%
“…5,9,13 In another study, only 44% of general dentists reported using a rubber dam for all root canal treatments. 14 Several studies found that dentists do not use sealants for caries prevention and treatment for adults or children 12,15,16 as often recommended by evidence-based guidelines. 1,17 …”
Section: Introductionmentioning
confidence: 99%